Imaging of the boron doping in silicon using low energy SEM - Müllerová, Ilona; El-Gomati, Mohamed M; Frank, Ludĕk (Ultramicroscopy, 2002)
Scanning electron imaging of plan views of boron-doped patterns in silicon is examined, together with the mechanism of formation of the electronic contrast in this kind of structures. Main to-date published results are critically reviewed and new data are presented concerning the secondary, backscattered and total-emission electron contrasts, including their qualitative and quantitative behaviour, particularly in the low energy range achieved with the help of the cathode lens (the scanning low energy electron microscopy mode, SLEEM). Surface analysis of the structure by means of Auger electron spectrometer has been performed, too, both before and after ion beam bombardment. The scanning electron microscope micrographs, acquired after the oxide mask removal in HF, are examined in a variety of detection modes, aiming at identification of the signal component primarily bearing the contrast. The energy dependence of the contrasts is presented as well as its change owing to alteration in the vacuum conditions. The most important findings include an extremely high contrast obtained in the SLEEM mode and even more enhanced under medium vacuum conditions at which the carbonaceous layer of surface contamination plays its role. The observed phenomena are partly explained in the frame of the "flat band" model of a passivated surface. The increased contrast in the SLEEM mode is understood as connected with the above-surface electric field of the cathode lens, generating space charge layers inside the semiconductor. In addition, charge carriers, injected via the primary electron beam, are considered as influencing the contrast vs. energy dependence.